Spoilage indicator bacteria in farmed Atlantic salmon (Salmo salar) stored on ice for 10 days. (February 2019) - Fogarty, Colin; Whyte, Paul; Brunton, Nigel; Lyng, James; Smyth, Conor; Fagan, John; Bolton, Declan
Abstract: This study investigated the growth of indicator and spoilage bacteria on whole Atlantic salmon ( Salmo salar) stored aerobically at 2 °C. On days 0, 2, 3, 6, 8 and 10 microbiological analysis was carried out on inner flesh and outer skin samples as well as outer skin swabs (25 cm 2 surface areas). Mesophilic total viable counts (TVCm ) on skin, flesh and swab samples increased from 1.9, 1.1 and 2.7 log10 CFUcm 2 to 6.0, 5.1 and 5.7 log10 CFU/cm 2 after 10 days, respectively. Psychrotrophic counts (TVCp ), increased from 2.2, 1.8 and 3.1 log10 CFU/cm 2 to 6.2, 5.3 and 5.9 log10 CFU/cm 2, for skin, flesh and swab samples respectively. Hydrogen sulphide producing bacteria (HSPB), lactic acid bacteria (LAB), Pseudomonas spp., Brochothrix thermosphacta and Photobacterium spp. grew well with similar growth rates (mean generation times of 17.2–26 h). It was concluded that the shelf-life of salmon at 2 °C was approximately 10 days and that HSPB, LAB, Pseudomonas spp ., Br. thermosphacta and Photobacterium spp. may be a better indicator of fish spoilage rather than TVC growth, with a count of 5–6 log10 CFU/cm 2 indicating the end of shelf-life. Highlights: Chilled and aerobically stored salmon had a shelf-life of approximately 10 days. HSPB, LAB, Pseudomonas spp., Br. thermosphacta and Photobacterium spp. were a better indicator of fish spoilage. Spoilage bacterial counts of 5–6 log10 CFU/cm 2 indicated the end of shelf-life.